EVALUASI GERAKAN LITERASI SEKOLAH UNTUK MENINGKATKAN MINAT BACA PESERTA DIDIK DI SD NEGERI GENDONGAN 01 SALATIGA MENGGUNAKAN MODEL CIPP - Anwar, Retno; Astuti, Suhandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to evaluate the School Literacy Movement program at SD Negeri Gendongan 01 Salatiga, Salatiga City. This research uses the CIPP model with qualitative descriptive methods. The data is sourced through interviews, observation and documentation, then the data is analyzed using qualitative descriptive analysis. The research results show that this context evaluation aims to improve students' abilities in literacy activities, for the evaluation of input facilities and infrastructure are quite adequate but need further improvement. In the process evaluation, students have carried out reading activities for 15 minutes before learning begins, and for product evaluation, the school's goal has been achieved, namely students become enthusiastic or motivated to read books. The inhibiting factor in this program is that the existing books never change, therefore it is necessary to rotate books. The School Literacy Movement  program at SD Negeri Gendongan 01 Salatiga is categorized as quite good, because the program has achieved the expected goals, but even so there is a need for program improvement.   Keywords : evaluation, CIPP model, school literacy